ESTIMATION OF PREVALENCE AND PATTERN OF TOBACCO USE: A CROSS-SECTIONAL STUDY AMONG SCHOOL ADOLESCENTS - Kumar, Vinod; Jain, Mayank; Jain, Manish; Garg, Kapil (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective of the study was to estimate prevalence and pattern of tobacco use among school-going adolescents and to assess their knowledge of harmful effects of tobacco. Over the world, tobacco kills more than 8 million people every year. A WHO report on tobacco consumption mention that tobacco consumption in India will continue to increase at 2.4% per annum and most of the new users will be school children. Methods: A cross-sectional study was carried out at government schools in urban and rural field practices areas of Jhalawar Medical College, Jhalawar. A semi-structured questionnaire pertaining information regarding age, sex, use of tobacco, knowledge of hazards, etc., was used for data collection. Results: Out of the 337 students, 15.1% reported an experience of any type of tobacco use. 8.61% students use smoking form of tobacco, 6.52% student use smokeless tobacco, and 1.48% of students use both form of tobacco. The difference of tobacco use among boys and girls student was statistically significant. Most common influential factor for tobacco use was peer pressure among the tobacco user. Out of the 51 tobacco users, adolescent students 31.37% have desire to quit tobacco. Conclusion: High prevalence of tobacco use among school-going students was alarming situation. The desire to quit tobacco among adolescent was very low.